Ten-year retrospective study on mandibular fractures in central Taiwan. Issue 7 (July 2020) - Chen, Yi-Tzu; Chiu, Yu-Wei; Chang, Yu-Chao; Lin, Chiao-Wen
Objective: To analyse the epidemiology of mandibular fractures and the correlation between combined fractures during a 10-year period in central Taiwan. Methods: This retrospective study analysed data collected from the medical records of patients that had mandibular fractures between January 2007 and October 2017. Data on age, sex, cause of injury, anatomical site of fracture, treatment and complications were obtained and analysed. Results: A total of 265 patients who received treatment were included in the study. The mean ± SD age was 30.08 ± 13.47 years (range, 6–70 years) and the 21–30 years age group showed the highest incidence of mandibular fractures. The male-to-female ratio was 1.25:1. Road traffic accidents were the most common cause of fracture (206 of 265; 77.74%). The symphysis and parasymphysis area was the most common fracture site (169 of 420; 39.29%). Single-site fracture represented slightly more than 50% of the total 420 fractures. The most frequent combination of two fractures was an angle fracture combined with a symphysis and parasymphysis fracture (29 of 106 double fracture patients [27.36%]). There was a weak positive association between several combinations of fractures. Conclusions: A better understanding of the influence of age and sex on the mechanism of injury is of great clinical importance in the assessment and diagnosis of fractures.